Biological and Genomic Characterisation of Curtobacterium flaccumfaciens Infecting Wheat - Fernandez, Franco Daniel (2025)
Several phytopathogenic bacteria have been reported worldwide affecting wheat (Triticum aestivum L.), causing significant yield losses. Over the past 5–6 years, symptoms resembling bacterial mosaic, characterised by small yellow lesions with indefinite margins scattered across the leaf, have been observed in wheat plants in one of the main producing areas in Argentina, with an incidence of 10% to 20%. This emerging disease has raised concern among producers and technicians. In this study, a bacterium was isolated from symptomatic seeds, and biochemical, molecular, and genomic techniques were used to identify the causal agent. Pathogenicity tests were conducted on wheat and soybean plants through leaf infiltration, demonstrating that the strain caused disease in wheat but not in soybean. Using a combination of MALDI-TOF MS, the API 20 NE test, 16S rRNA gene, and whole-genome sequencing confirmed the pathogen as Curtobacterium flaccumfaciens. Phylogenomic and genome-to-genome comparisons showed the strain sequenced grouped within the type strain sequence of C. poinsettiae CFB 2403. To our knowledge, this is the first report of Curtobacterium flaccumfaciens as a pathogen on wheat in Argentina. This research contributes significantly to understanding this phytosanitary problem with detailed information on the pathogen, using advanced technology and new reclassifications of pathogenic bacteria, which will allow the development and implementation of effective management strategies in the future.